Identity viewed askew : a debate with special reference to a feminist theological organisation : a thesis presented in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Sociology, Department of Social and Cultural Studies, Massey University, Albany, New Zealand - Leggatt-Cook, Chez (Massey University. School of Social and Cultural Studies, 2005)
A critical task in the formation of any political group is the determination and articulation of group identity, purpose and goals. In holding that identity is impervious to capture, much poststructuralist thought has little to contribute to an understanding of the precise processes and ongoing tensions involved in such drives for representation. The essentialism debate in feminist theory, for instance, has been primarily concerned with determining which conceptualisation of women's subjectivity will best facilitate feminism's political goals. However, under the influential feminist deconstructive perspective, a dilemma emerges regarding how an anti-essentialist notion of femininity might be reconciled with the essentialism required for a distinctly feminist voice. Alternatively, post-Lacanian psychoanalysis views subjectivity as an effect of fundamentally irresolvable antagonisms in language, allowing the emphasis to shift from the (attempted) reconciliation of irresolvable tensions to the identification of mechanisms that work to conceal those tensions, thereby permitting a sense of subjectivity to be articulated. This thesis explores the methodological implications of these theoretical debates, examining how the psychoanalytic line of questioning might be used to analyse feminist identity in an empirical setting. Research was conducted with the Women's Resource Centre (WRC) based in Auckland, New Zealand, an organisation originally established to provide feminist theology resources to women undergoing theological education. Using a conversational methodology and the observation of material expressions of identity, the research attempts to view the Centre's identity 'askew.' In doing so, it considers the creative yet eventually regressive impact of the postmodern privileging of difference and multiplicity on the feminist identity of the Centre. Referring specifically to the changing expression of the Centre's identity (in promotional material, funding applications and the WRC Story), the thesis traces the effects of ideological tension (in incorporating more inclusive notions of justice with feminist politics) and organisational change (dispersion of the original community, high staff turnover, shift in organisational culture, funding difficulties). Wider implications of the research for voluntary and feminist organisations are indicated, along with an evaluation of post-Lacanian psychoanalysis for the empirical study of identity and for the overarching theoretical concerns of the thesis.
Keywords: Organisational identity; Feminist identity; Group identity; Subjectivity; Psychoanalysis; Zizek; 370106 Sociological methodology and research methods